(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Advancement in technology and changes in knowledge delivery are making it imperative for teachers to acquire new skills and knowledge to meet the needs of today’s students. Teachers in rural areas rarely take advantage of professional development opportunities provided for them. This study explored the perspective of rural teachers on the constraints of accessing professional development programmes in order to situate Open Distance Learning (ODL) as an alternative method of delivering professional development training. Rubenson’s Recruitment Paradigm (1977), Cross’ Chain-of- Response Model (1981) and Darkenwald and Merriam’s Psychosocial Interaction Model (1982) guided the study. The study employed survey research design to answer the research questions raised. The population consisted of all teachers in public secondary schools in the rural areas of Lagos state. Ten secondary schools were randomly selected for the study. Twenty teachers were purposively selected from each school, making a total of 200 teachers. A self-developed questionnaire was employed to collect data. Data collected were analysed using descriptive statistics. The study revealed that teachers in the rural areas rarely go for professional development programmes as a result of constraints such as lack of time, lack of funds, inability to forego family time for development training and teachers’ disposition. Based on the findings, it was suggested that the effects of these barriers can only be mitigated through ODL which allows teachers to learn whatever, wherever, whenever, and however they want to learn through information communication technology.